Controversies Surrounding Renal Replacement Therapy in the Critically Ill Patient - Iacovella, Gina M.; Kumar, Neelja (Seminars in Respiratory and Critical Care Medicine, 2019)
Acute kidney injury (AKI) commonly occurs in the intensive care unit and is associated with significant morbidity and mortality. Patients with AKI often require initiation of dialysis to control electrolytes, metabolic abnormalities, and volume status. This review will discuss controversies in renal replacement therapy (RRT), including timing of dialysis initiation, dialysis modality and dose, nonrenal indications for dialysis, and the patient population best suited for RRT therapy.
Keywords: acute kidney injury; intensive care unit; renal replacement therapy